2019
DOI: 10.1186/s12879-019-3881-y
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of TB-LAMP for pulmonary tuberculosis: a systematic review and meta-analysis

Abstract: BackgroundThe need for a rapid, molecular test to diagnose tuberculosis (TB) has prompted exploration of TB-LAMP (Eiken; Tokyo, Japan) for use in resource-limited settings. We conducted a systematic review to assess the accuracy of TB-LAMP as a diagnostic test for pulmonary TB.MethodsWe analyzed individual-level data for eligible patients from all studies of TB-LAMP conducted between Jan 2012 and October 2015 to compare the diagnostic accuracy of TB-LAMP with that of smear microscopy and Xpert MTB/RIF® using 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 13 publications
1
42
1
Order By: Relevance
“…Currently, the WHO only endorses the use of two rapid molecular tests for the diagnosis of pulmonary TB, which were Xpert MTB/RIF and the commercialized TB-LAMP assay [ 9 ]. According to previous studies, both had shown comparable performance in smear-positive samples, but higher sensitivity was shown in Xpert MTB/RIF than in the LAMP test [ 6 , 12 ]. Xpert MTB/RIF has been endorsed for use in the diagnosis of TB in many countries, including Thailand [ 4 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, the WHO only endorses the use of two rapid molecular tests for the diagnosis of pulmonary TB, which were Xpert MTB/RIF and the commercialized TB-LAMP assay [ 9 ]. According to previous studies, both had shown comparable performance in smear-positive samples, but higher sensitivity was shown in Xpert MTB/RIF than in the LAMP test [ 6 , 12 ]. Xpert MTB/RIF has been endorsed for use in the diagnosis of TB in many countries, including Thailand [ 4 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…These nucleic amplification techniques were known for yielding rapid and accurate TB diagnosis, which would overcome the limitations of classical methods (ie, insensitivity for smear microscopy and lengthy incubation period for TB culture). However, several obstacles remain for the application of these molecular tests as point-of-care testing in community settings due to their complexity to execute and substantial requirements for financial and personnel resources [ 3 , 6 ]. Loop-mediated isothermal amplification (LAMP) assay is another recently developed nucleic acid amplification technique.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The LAMP-MTBC detection kit, which is endorsed by the WHO, targets the gyrB gene and IS regions of the Mtb complex genome. In this assay, the amplified product is visualized with the naked eye or under ultraviolet (UV) light [47]. In the CPA-based TB diagnostic system, PCR amplification is done at a single temperature using multiple primers and probes of Mtb.…”
Section: Molecular Biological Diagnosis Of Active Tbmentioning
confidence: 99%
“…Isothermal amplification techniques, such as loop-mediated isothermal amplification (LAMP), eliminated the shortcomings posed by traditional smear microcopy, culture-and PCR-based assays, and has been endorsed by the WHO (World Health Organization) in 2016 (Notomi et al 2000;World-Health-Organizaion 2016). Although many LAMP-based assayshave been reported for reliable diagnostic of MTB (Yadav et al 2017;Rakotosamimanana et al 2019;Shete et al 2019;Bojang et al 2016), the TB-LAMP results were determined by agarose gel electrophoresis, colorimetric indicator (SYBR green I or calcein dyes) and real-time turbidity. Particularly, analysis of LAMP result using agarose gel electrophoresis requires an additional process, and easily leads to carryover contamination; recognition of LAMP amplification using colorimetric indicator is potentially subjective, and easily produces ambiguous judgment; detection of the LAMP products using real-time turbidity needs an expensive optical instrument (Zhang et al 2014).…”
Section: Introductionmentioning
confidence: 99%